ナンキョク オキアミ リョウ デ コンカク サレタ ギョルイ ニ ツイテ II. ツブマトウダイ Xenocyttus nemotoi ABE オヨビ フタタビ カラスコオリウオ Neopagetopsis ionah NYBELIN ニ ツイテ - 阿部, 宗明; アベ, トキハル; 鈴木, 満平; スズキ, マンペイ; Abe, Tokiharu; Suzuki, Manpei (1981)
P(論文) ツブマトウダイ(Xenocyttus nemotoi ABE)は, 1957年マッコウクジラの胃袋から得られた唯一の標本に基づいて命名発表されたが, その後, ソ連の学者による報告があり, 他方最近になって, オキアミ漁に混獲されるものが相当数見られた。それらのうち魚学および食品化学研究用に標本29個体を採集し, 他方深海トロールで得られた1尾の写真を入手した。本種の生活史, 分布等については不明な点が多いが, 上記の資料について記し, また最近の他の研究者による知見を紹介する。肉の一般成分分析は3個体について実施し, 水分84.2%, 粗タンパク質9.6%, 粗脂肪3.8%, 灰分1.1%(いずれも平均値)の結果を得た。また筋肉と体全体を包むように存在する硬い皮下組織層の熱伝導度を測定, 比較したところ, 両者には明らかに差は認められたが, その違いは大きいものではなかった。次に, カラスコオリウオ(Neopagetopsis ionah NYBELIN)については, 前報作製の際, 見落したソ連の文献がいくつかあり, その後出た報告もある。追加標本も日本のオキアミ調査の際にかなり多数得られたし, オキアミ漁と直接関係はないが, ロス海のトロールで6個体(標準体長165～435mm)をも入手したので, これらについて簡単に報告する。なおオキアミ漁の際, カラスコオリウオはツブマトウダイより数多く見られることが確かめられた。また, カラスコオリウオの鰓条骨数は8または9であるが, 前報で述べたように, 9の場合の方がやはり多く, 9個ある場合には最下のものが発達不十分で, 末端は鰓条膜辺縁に到達しない場合が多いことを知った。 Since the description of Xenocyttus nemotoi ABE in 1957,there have been but a few records of this oreosomatid fish. Recently it is taken from time to time along with the Antarctic krill, and 29 specimens have been received for study. Their size varies very little, standard length being 113mm to 180mm. This species is now known to occur off Patagonia as well. They are thought to be the young of a much larger fish. Their diet is copepods. In the absence of the holotype of its close ally, Pseudocyttus maculatus GILCHRIST, it is thought advisable to discuss the relationships of Xenocyttus with the other members of the Oreosomatidae and Zeiformes in the future. The flesh of three specimens of Xenocyttus nemotoi measuring some 150mm in standard length contains water (84.2%), crude protein (9.6%), crude fat (3.8%) and crude ash (1.1%). The subcutaneous tissue is fairly hard, and its heat conductivity is ca. 0.60 (kcal/m・h・℃) as against ca. 0.65 in the flesh. Many specimens of Neopagetopsis ionah NYBELIN have been collected since the publishing of the previous paper of this series. It is met with oftener than Xenocyttus nemotoi at fishing grounds of the Antarctic krill. The number of branchiostegals is oftener 9 on either side. At times it is 8 on either side, or 9 on one side and 8 on the other. ...